The Gain-of-Function R222S Variant in Scn11a Contributes to Visceral Hyperalgesia and Intestinal Dysmotility in Scn11aR222S/R222S Mice - Zhao, Chenyu; Jin, Jishuo; Hu, Haoye; Zhou, Xi; Shi, Xiaoliu (Frontiers in Neurology, 2022)
Background The SCN11A gene encodes the α-subunit of the Nav1. 9 channel, which is a regulator of primary sensory neuron excitability. Nav1.9 channels play a key role in somatalgia. Humans with the gain-of-function mutation R222S in SCN11A exhibit familial episodic pain. As already known, R222S knock-in mice carrying a mutation orthologous to the human R222S variant demonstrate somatic hyperalgesia. This study investigated whether Scn11aR222S/R222S mice developed visceral hyperalgesia and intestinal dysmotility. Methods We generated Scn11aR222S/R222S mice using the CRISPR/Cas9 system. The somatic pain threshold in Scn11aR222S/R222S mice was assessed by Hargreaves' test and formalin test. The excitability of dorsal root ganglia (DRG) neurons was assessed by whole-cell patch-clamp recording. Visceralgia was tested using the abdominal withdrawal reflex (AWR), acetic acid-induced writhing, and formalin-induced visceral nociception tests. Intestinal motility was detected by a mechanical recording of the intestinal segment and a carbon powder propelling test. The excitability of the enteric nervous system (ENS) could influence gut neurotransmitters. Gut neurotransmitters participate in regulating intestinal motility and secretory function. Therefore, vasoactive intestinal peptide (VIP) and substance P (SP) were measured in intestinal tissues. Results The R222S mutation induced hyperexcitability of dorsal root ganglion neurons in Scn11aR222S/R222S mice. Scn11aR222S/R222S mice exhibited somatic hyperalgesia. In addition, Scn11aR222S/R222S mice showed lower visceralgia thresholds and slowed intestinal movements when compared with wild-type controls. Moreover, Scn11aR222S/R222S mice had lower SP and VIP concentrations in intestinal tissues. Conclusions These results indicated that Scn11aR222S/R222S mice showed visceral hyperalgesia and intestinal dysmotility.